INNOVATIVE APPROACH TO EVALUATION OF MANAGEMENT DECISIONS (theoretic and practical issues) - S. L. Savin (Модернизация, инновация, развитие, 2016)
Effectiveness of management decisions may be assessed through such criteria as admissibility, efficiency and optimization effect. Management decision expressed in qualitative form is optimal only in case the aim is single, the restrictions are formulated distinctly and respective mathematical extremity task is solved. However, it is quite often that many economic phenomena, processes and relations are hardly expressed in quantitative manner. Management decisions are to be assessed qualitatively on the basis of empirical and theoretical criteria.